Death's end eaudiobook - Liu, Cixin (Remembrance of Earth's Past, 2016)
The inspiration for the Netflix series 3 Body Problem ! Over 1 million copies of the Three-Body Problem series sold in North America PRAISE FOR THE THREE-BODY PROBLEM SERIES: "A mind-bending epic." — The New York Times " War of the Worlds for the 21st century." — The Wall Street Journal "Fascinating." — TIME "Extraordinary." — The New Yorker "Wildly imaginative." —Barack Obama "Provocative." — Slate "A breakthrough book." —George R. R. Martin "Impossible to put down." — GQ "Absolutely mind-unfolding." — NPR "You should be reading Liu Cixin." — The Washington Post The New York Times bestselling conclusion to the groundbreaking, Hugo Award-winning series from China's most beloved science fiction author, Cixin Liu. Half a century after the Doomsday Battle, the uneasy balance of Dark Forest Deterrence keeps the Trisolaran invaders at bay. Earth enjoys unprecedented prosperity due to the infusion of Trisolaran knowledge. With human science advancing daily and the Trisolarans adopting Earth culture, it seems that the two civilizations will soon be able to co-exist peacefully as equals without the terrible threat of mutually assured annihilation. But the peace has also made humanity complacent. Cheng Xin, an aerospace engineer from the early twenty-first century, awakens from hibernation in this new age. She brings with her knowledge of a long-forgotten program dating from the beginning of the Trisolar Crisis, and her very presence may upset the delicate balance between two worlds. Will humanity reach for the stars or die in its cradle? The Three-Body Problem Series The Three-Body Problem The Dark Forest Death's End Other Books by Cixin Liu Ball Lightning Supernova Era To Hold Up the Sky The Wandering Earth A View from the Stars A Macmillan Audio production from Tor Books